DESIGN OF AUTOMATIC DISINFECTION ROBOT WITH COMPLETE COVERAGE PATH PLANNING REINFORCEMENT LEARNING ALGORITHM IN SYSTEM ON CHIP - Puji Laksono, Satrio
The need for disinfection during the COVID-19 pandemic has increased very high. One of the places that requires a routine disinfection process is the doctor's office in the hospital. Disinfection activities are still mostly done by humans manually. This has a negative impact on the perpetrators of disinfection in terms of health, so a tool is needed that can replace humans as the perpetrators of disinfection. Autonomous disinfection robot was chosen to replace the disinfectant, by using a complete coverage path planning algorithm. Complete Coverage Path Planning (CCPP) is an algorithm that can determine the path traversed by a robot so that it can pass through the entire room by avoiding existing objects. The application of CCPP in robotic applications has been widely applied to robotic vacuum cleaners, lawn mowers, mine disposal robots, autonomous harvesters, disinfection robots, and many more. In this final project, the CCPP algorithm with Reinforcement Learning on the System on Chip will be applied to become a disinfection robot that moves autonomously, with coverage area 78%.